1992
DOI: 10.1037/0278-6133.11.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to juvenile rheumatic disease: A controlled evaluation of functional disability with a one-year follow-up.

Abstract: Compared the adaptation of 165 patients with juvenile rheumatic disease (JRD) to that of their healthy siblings. Patients were divided into those with mild functional disability and those with moderate/severe disability. Adaptation in several domains was assessed by parents and children on two occasions 1 year apart. The adjustment difficulties of the JRD children were limited primarily to social functioning but appeared also in the psychological and family problems domains. Compared to "mild" patients, "moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2
4

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 28 publications
1
24
2
4
Order By: Relevance
“…These results failed to confirm our hypothesis that children with JRA have problematic peer relation- (20,59), our data suggest that JRA does not adversely impact the ability to get along with peers. Our findings are similar to those reported by Harris et al (22).…”
Section: Discussioncontrasting
confidence: 57%
“…These results failed to confirm our hypothesis that children with JRA have problematic peer relation- (20,59), our data suggest that JRA does not adversely impact the ability to get along with peers. Our findings are similar to those reported by Harris et al (22).…”
Section: Discussioncontrasting
confidence: 57%
“…Depressive episodes become less common in later life, suggesting that experience enables patients to learn to cope with their disease more effectively. This supports the hypothesis suggested by Timko et al (1992) that psychosocial adjustments continue with time as an individual adapts to his or her disease.…”
Section: Moodsupporting
confidence: 84%
“…Social support from the family is a predictor of global self-worth, whereas patient depression is related to poor social support and family conflict (Cuneo and Schiaffino, 2002). Previously, parental questionnaire-based studies have suggested that there is an association between parental distress and a child's psychological maladjustment (Timko et al, 1992). More recently, it has been suggested that the use of parental reports for measuring a child's psychological adjustment introduces a bias in the reporting of the child's psychological state, with any maladjustment in the parent often being falsely transposed to the child.…”
Section: Familymentioning
confidence: 99%
“…A versão pediátrica do Health Assessment Questionnaire 11,18,19 , o Childhood Health Assessment Questionnaire (CHAQ), com adaptação cultural em diversos idiomas 20 , possibilita, com vantagem, o uso deste instrumento para avaliação de artrite crônica desde a infância até a vida adulta. Confirmamos, no presente estudo, a sua aplicabilidade, avaliando o perfil da capacidade funcional de acordo com a percepção dos pais nas consultas de rotina.…”
Section: Discussionunclassified